2018
DOI: 10.1007/s11046-018-0259-4
|View full text |Cite
|
Sign up to set email alerts
|

Culture Supernatants of Lactobacillus gasseri and L. crispatus Inhibit Candida albicans Biofilm Formation and Adhesion to HeLa Cells

Abstract: The culture supernatants of L. gasseri and L. crispatus inhibited C. albicans biofilm formation by downregulating biofilm formation-related genes and C. albicans adhesion to HeLa cells. These findings support the notion that Lactobacillus metabolites may be useful alternatives to antifungal drugs for the management of VVC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 31 publications
6
30
0
Order By: Relevance
“…can reduce the number of hyphae formed by C. albicans (Vilela et al 2015;Ribeiro et al 2017) by releasing antimicrobial compounds, which create an adverse microenvironment for pathogens (Mastromarino et al 2002;do Carmo et al 2016). Although some molecules as biosurfactants, hydrogen peroxide, lactic acid, acetic acid and bacteriocins, are already described, further studies involving the acquisition and characterization of new molecules are needed as well as elucidation of their inhibitory activities against C. albicans, particularly in terms of biofilm formation, filamentation capacity and infection potential (James et al 2016;Liang et al 2016;Eryilmaz et al 2018;Matsuda et al 2018).…”
Section: Biofilms and Hyphae Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…can reduce the number of hyphae formed by C. albicans (Vilela et al 2015;Ribeiro et al 2017) by releasing antimicrobial compounds, which create an adverse microenvironment for pathogens (Mastromarino et al 2002;do Carmo et al 2016). Although some molecules as biosurfactants, hydrogen peroxide, lactic acid, acetic acid and bacteriocins, are already described, further studies involving the acquisition and characterization of new molecules are needed as well as elucidation of their inhibitory activities against C. albicans, particularly in terms of biofilm formation, filamentation capacity and infection potential (James et al 2016;Liang et al 2016;Eryilmaz et al 2018;Matsuda et al 2018).…”
Section: Biofilms and Hyphae Formationmentioning
confidence: 99%
“…Most of these genes either enable adhesion and invasion of the host cell or modify the pathogenic form to avoid host defence mechanisms, in addition to having the ability to form biofilms on biotic and abiotic surfaces (Mayer et al 2013). To elucidate the molecular mechanisms involved in the antifungal effects of probiotic bacteria, especially Lactobacillus sp., several in vitro studies have focused on analysis of the expression of the virulence genes of C. albicans (Kohler et al 2012;James et al 2016;Ribeiro et al 2017;Wang et al 2017;de Barros et al 2018;Matsuda et al 2018;Rossoni et al 2018). Kohler et al (2012) investigated the molecular mechanisms of C. albicans growth inhibition by the probiotic strains Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 using genome-wide expression analyses.…”
Section: Interference With Virulence Genesmentioning
confidence: 99%
“…L. crispatus and L. gasseri are commensal bacteria found in both human GI tract (Walter, 2008) and lower female urogenital tract. Their implication on women's health have been explored in the recent years (Stapleton et al, 2011;Matsuda et al, 2018;Phukan et al, 2018;Takada et al, 2018). Preliminary clinical trials have shown that intro-vaginal probiotic treatment with L. crispatus (intravaginal suppository probiotic Lactin-V; Osel) could significantly lower the reoccurrence rate of urinary tract infections in premenopausal women (Stapleton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…L. gasseri American Type Culture Collection (ATCC) 9857 has been found to significantly inhibit the adhesion of Trichomonas vaginalis to human vaginal ectocervical cells (Phukan et al, 2018). Supernatant of L. crispatus JCM 1185 and L. gasseri JCM 1131 significantly inhibited the colonization of Candida albicans by reducing the expression of biofilm formation-related genes (Matsuda et al, 2018). It is recognized that bacteria residing in different environments could develop niche-specific adaptation, providing competitive advantages for colonizing each niche (Oh et al, 2010;Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested that probiotic supernatants have antipathogenic properties [4], which implies that probiotics may inhibit bio lm formation through cell-cell communication. However, there has been little progress in this eld to date.…”
Section: Introductionmentioning
confidence: 99%